Association of Blood Glucose Control with Wound Healing in Patients with Diabetes Mellitus - Wiyono, Mohamad; Setyawan, Yuswanto (Poltekkes Kemenkes Banjarmasin, 2025)
This study aimed to investigate the relationship between glycemic control and wound healing in patients with diabetes mellitus. A cross-sectional study was conducted at a diabetic wound clinic in Pasuruan from March to May 2025 involving 164 participants. Data were collected on HbA1c levels and wound healing outcomes, and analyzed using both Chi-square and Spearman correlation tests. The results showed a significant association between HbA1c categories and wound healing outcomes, with higher HbA1c levels linked to delayed healing. Spearman analysis confirmed a moderate negative correlation between continuous HbA1c values and wound healing scores, indicating that poor glycemic control impairs tissue repair. These findings highlight the importance of maintaining optimal blood glucose levels to accelerate wound recovery and prevent complications. Clinical recommendations include continuous glucose monitoring, individualized glycemic management, patient education, and structured self-care programs. Future research should employ multi-center designs and objective wound assessment tools to strengthen evidence and generalizability. The study provides essential insights for both clinical practice and public health strategies aimed at improving diabetic wound outcomes.